In-vitro assessment of the thrombolytic efficacy of therapeutic ultrasound. Issue 178 (June 2019) - Salman-Kesner, Nava; Zaltsman, Masha-Maria; Ertracht, Offir; Atar, Shaul
Abstract: Background: Ultrasound is mainly used as a diagnostic tool. Several studies demonstrated that therapeutic ultrasound (TUS) can enhance thrombolysis, but the optimal mechanical parameters to achieve this biological effect are still unknown. Methods: We assembled 46 blood clots in a closed in-vitro circulatory model. Clots were randomly divided into 7 groups, control group and six TUS groups of three frequencies (0.3, 0.5, 0.7 MHz) and six intensities (0.75, 1.5, 3, 237.7, 475, 950 W/cm 2 ). Treatment was composed of 12 repetitions, 5 min US application and 3 min pause, lasting 93 min in total. Clots' weight and flow rate were measured before and after the treatment. Results: Mean initial clot weight (0.318 ± 0.129 g) and flow (0.53 ± 0.31 ml/min) were comparable among the experimental groups. We found a final clot weights reduction (0.15 ± 0.05, 0.16 ± 0.06, 0.09 ± 0.07, 0.21 ± 0.09, 0.17 ± 0.09, 0.17 ± 0.07 and 0.18 ± 0.02 g in groups 1 through 6, respectively) and a flow increase (30.61 ± 19.76, 52.1 ± 25.44, 28.78 ± 8.15, 43.93 ± 20.03, 40.86 ± 18.25 and 45.10 ± 22.20 ml/min in groups 1–6, respectively) in all TUS groups. Clot weight change (%) and flow increase reveals that the TUS profile f  = 0.5 MHz I = 1.5 W/cm 2 was most efficacious. In the control group, clot weight change was +6.3% of baseline and flow increase of 4.4% of baseline, whereas −75.4% of baseline and 209.3% of baseline in the f  = 0.5 MHz I = 1.5 W/cm 2 profile were noted, respectively. Conclusions: Our study proved that TUS at low frequency (0.5 MHz) is most effective, whereas changing the intensity of TUS has only a minor effect on clot lysis magnitude. Highlights: Therapeutic ultrasound, without the use of a fibrinolytic drug, may be an effective method for clot lysis. Low-frequency therapeutic ultrasound (0.5 MHz) is most effective for thrombolysis. The intensity of therapeutic ultrasound has only a minor effect on the magnitude of clot lysis. The proposed therapeutic ultrasound profile may be clinically applicable.